POS-tagging model: Flair - Språkbanken Text (University of Gothenburg, 2024)
Models
Flair is a powerful NLP library. We provide two Flair models for Swedish part-of-speech tagging.
flair_eval is trained on SUC3 with Talbanken_SBX_dev as dev set. The advantage of this model is that it can be evaluated, using Talbanken_SBX_test or SIC2. The evaluation results are reported in the table below.

Test set
Exact match
POS
MSD

Talbanken_SBX_test
0.978
0.987
0.990

SIC2
0.926
0.940
0.964

Read more about the evaluation here.
flair_full is trained on SUC3 + Talbanken_SBX_test + SIC2 with Talbanken_SBX_dev as dev set. We cannot evaluate the performance of this model, but we expect it to perform better than flair_eval, or at least not worse.
Using the models on your own
Download the model and follow the instructions from Flair. By default, Flair's own embeddings will be used (our experiments show that they provide the best results), but you may use other embeddings instead (or combine them). GPU is strongly recommended.

Models
Flair is a powerful NLP library. We provide two Flair models for Swedish part-of-speech tagging.
flair_eval is trained on SUC3 with Talbanken_SBX_dev as dev set. The advantage of this model is that it can be evaluated, using Talbanken_SBX_test or SIC2. The evaluation results are reported in the table below.

Test set
Exact match
POS
MSD

Talbanken_SBX_test
0.978
0.987
0.990

SIC2
0.926
0.940
0.964

Read more about the evaluation here.
flair_full is trained on SUC3 + Talbanken_SBX_test + SIC2 with Talbanken_SBX_dev as dev set. We cannot evaluate the performance of this model, but we expect it to perform better than flair_eval, or at least not worse.
Using the models on your own
Download the model and follow the instructions from Flair. By default, Flair's own embeddings will be used (our experiments show that they provide the best results), but you may use other embeddings instead (or combine them). GPU is strongly recommended.
Ordklasstaggningsmodell: Flair
Keywords: Language Technology (Computational Linguistics); model; Natural Language Processing; Språkbehandling och datorlingvistik